Repeated Endovascular Treatment of Early Recurrent Proximal Middle Cerebral Artery Occlusion: Case Report and Brief Review of the Literature - Fandler, Simon; Deutschmann, Hannes; Fazekas, Franz; Gattringer, Thomas (Frontiers in Neurology, 2018)
Mechanical thrombectomy (MT) is the gold standard treatment for large vessel occlusion (LVO) stroke of the anterior circulation. Whether MT can also be effectively and safely performed in early recurrent LVO is largely unclear. We present the case of a middle-aged patient who was successfully treated by MT for right proximal middle cerebral artery (MCA) occlusion with excellent outcome. One day after discharge (nine days after the first MT), the patient was readmitted with wake-up stroke. MRI again revealed right proximal MCA occlusion with severe diffusion-perfusion mismatch. Repeat MT was performed and once more led to almost full recovery. The recurrent strokes were attributed to exulcerated non-stenosing plaques in the ipsilateral internal carotid artery which prompted thromboendarterectomy. In an 18-months follow-up period, no further vascular events occurred. In conclusion, repeated MT for early recurrent LVO appears feasible in carefully selected patients. The collection of similar cases via registries would be desirable.